Recombinant adeno-associated virus-mediated microRNA delivery into the postnatal mouse brain reveals a role for miR-134 in dendritogenesis in vivo - Christensen, Mette; Larsen, Lars A.; Kauppinen, Sakari; Schratt, Gerhard (Frontiers in neural circuits, 2010)
Recent studies using primary neuronal cultures have revealed important roles of the microRNA pathway in the regulation of neuronal development and morphology. For example, miR-134 is involved in dendritogenesis and spine development in hippocampal neurons by regulating local mRNA translation in dendrites. The in vivo roles of microRNAs in these processes are still uninvestigated, partly due to the lack of tools enabling stable in vivo delivery of microRNAs or microRNA inhibitors into neurons of the mammalian brain. Here we describe the construction and validation of a vector-based tool for stable delivery of microRNAs in vivo by use of recombinant adeno-associated virus (rAAV). rAAV-mediated overexpression of miR-134 in neurons of the postnatal mouse brain provided evidence for a negative role of miR-134 in dendritic arborization of cortical layer V pyramidal neurons in vivo, thereby confirming previous findings obtained with cultured neurons. Our system provides researchers with a unique tool to study the role of any candidate microRNA in vivo and can easily be adapted to microRNA loss-of-function studies. This platform should therefore greatly facilitate investigations on the role of microRNAs in synapse development, plasticity and behavior in vivo.
Gesehen am 20.03.2023